2017
DOI: 10.3748/wjg.v23.i19.3407
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between adipose tissue dysfunction, vitamin D deficiency and the pathogenesis of non-alcoholic fatty liver disease

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide. Its pathogenesis is complex and not yet fully understood. Over the years many studies have proposed various pathophysiological hypotheses, among which the currently most widely accepted is the “multiple parallel hits” theory. According to this model, lipid accumulation in the hepatocytes and insulin resistance increase the vulnerability of the liver to many factors that act in a coordinated and cooperative manner to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 167 publications
2
62
1
2
Order By: Relevance
“…Vitamin D also has anti-inflammatory and immune-modulatory activity. A lower vitamin D level results in adipose tissue dysfunction and subsequent chronic inflammation, which may also contribute to the development of NAFLD (20,25,26). Furthermore, ananimal study indicated that vitamin D deficiency is related to the development and progression of NAFLD through the activation of TLR2 and TLR4 via CD14/ LBP, and stimulation of the downstream inflammatory signaling molecules involved with steatosis in the liver (27).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D also has anti-inflammatory and immune-modulatory activity. A lower vitamin D level results in adipose tissue dysfunction and subsequent chronic inflammation, which may also contribute to the development of NAFLD (20,25,26). Furthermore, ananimal study indicated that vitamin D deficiency is related to the development and progression of NAFLD through the activation of TLR2 and TLR4 via CD14/ LBP, and stimulation of the downstream inflammatory signaling molecules involved with steatosis in the liver (27).…”
Section: Discussionmentioning
confidence: 99%
“…Спільним патогенетичним механізмом розвитку ішемічної хвороби серця та неалкогольного стеатогепатиту являється активація процесів перекисного окиснення ліпідів на фоні дії агресивних вільних радикалів, що зумовлюється низькою функціональною активністю системи антиоксидантного захисту [4]. Одним із найбільш значущих чинників у патогенезі НАЖХП є ожиріння, яке посилює розвиток ІР [5]. У ряді досліджень відзначено, що резистентність до інсуліну є характерною особливістю НАЖХП, незалежно від наявності ожиріння [6].…”
Section: Original Researchunclassified
“…In particular, evidence has been accumulated that, in NAFLD, mitochondrial functionality is impaired mainly due to the increased mitochondrial oxidation deriving from greater FFA availability [10][11][12][13]. Furthermore, in NAFLD the oxidation of peroxisomes and microsomes occurring at the level of endoplasmic reticulum (ER) is stimulated by a greater availability of hepatic FFA, being the latter re-esterified in triglycerides and assembled in VLDL (very low density lipoproteins) [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%